2019
DOI: 10.1042/bsr20182172
|View full text |Cite
|
Sign up to set email alerts
|

Identification of key genes involved in type 2 diabetic islet dysfunction: a bioinformatics study

Abstract: Aims: To identify the key differentially expressed genes (DEGs) in islet and investigate their potential pathway in the molecular process of type 2 diabetes. Methods: Gene Expression Omnibus (GEO) datasets (GSE20966, GSE25724, GSE38642) of type 2 diabetes patients and normal controls were downloaded from GEO database. DEGs were further assessed by enrichment analysis based on the Database for Annotation, Visualization and Integrated Discovery (DAVID) 6.8. Then, by using Search Tool for the Retri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 37 publications
0
26
0
1
Order By: Relevance
“…The comparison method we adopted fully considered the in uence of genetics and environments. Although this comparison will overestimate the role of the genetic effects of the leptin receptor gene in T2DM and increase the di culty of comparison with other similar studies [57,58], we believe this is a simple and effective comparison strategy when the population's genetic background is not known clearly. So far, very limited studies have been performed with regard to detection of plasma proteins and lipids pro les in ZDF rats.…”
Section: Discussionmentioning
confidence: 99%
“…The comparison method we adopted fully considered the in uence of genetics and environments. Although this comparison will overestimate the role of the genetic effects of the leptin receptor gene in T2DM and increase the di culty of comparison with other similar studies [57,58], we believe this is a simple and effective comparison strategy when the population's genetic background is not known clearly. So far, very limited studies have been performed with regard to detection of plasma proteins and lipids pro les in ZDF rats.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, using the GSE20966 dataset, Ding et al (33) revealed DEGs that are enriched in the pancreatic secretion pathway, and that serpin family G member 1 and alanyl aminopeptidase membrane are associated with the development of T2D. In addition, Zhong et al (34) reported that ATP-citrate lyase is hub gene involved in the molecular mechanism of T2D. Based on previous studies, the characteristic of the PPI network were further analyzed in the present study, which identified additional hub genes, including ALB, IL-8, CD44, CCL2, HGF, CFTR, HIST1H2BN, MAPK11 and NTRK2.…”
Section: Discussionmentioning
confidence: 99%
“…We found alterations of Arhgef9, encoding Rho guanine nucleotide exchange factor 9, a guanine exchange factor for Cdc42. This is one of the few genes consistently identified in multiple surveys of diabetic islet gene expression (Zhong et al, 2019). Small G-proteins, such as Rho, Rac1, Cdc42, and Arf6 play important roles in cytoskeletal remodeling, vesicle fusion, and insulin exocytosis (Kowluru, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…S4). The latter included ARHGEF9, one of only 20 genes concordantly decreased in three independent RNA profiling datasets of type 2 diabetes patients (Zhong et al, 2019). 12 genes (Ttc22,Sel1l3,Rspo4,Pla2g4b,Nr1h4,Lad1,Jmjd7,Fut1,Elovl2,Dll4,Cacnb3,and Baiap2l2) were shared in common between the two comparisons (Table S7 and S8).…”
Section: Relevance To Human Type 2 Diabetes Gwasmentioning
confidence: 96%